EFEKTIVITAS IMPLEMENTASI PROGRAM PEMBERDAYAAN MASYARAKAT BERBASIS RUKUN WARGA (PMB-RW) - Fitria Ramadayani; Zaili Rusli; Febri Yuliani (Universitas Riau, 2018)
Effectiveness of Implementation of Community Empowerment Program Basedon Rukun Warga (PMB-RW). Community Empowerment Program based on Rukun Warga is aprogram of poverty eradication conducted by Pekanbaru city government through the process ofapproach of community empowerment pattern with financing from APBD Kota Pekanbaru,Provincial APBD, State Budget, State-Owned Enterprise and Corporate Social Responsibility(CSR) not binding. Therefore, through Mayor Regulation No. 44 of 2014 and RegionalRegulation No. 5 of 2016, the community-based community empowerment program (PMB RW)has the goal of creating harmony, security and peace, realizing the prosperity of the people ofPekanbaru City and creating a clean, healthy and beautiful environment . So with that purpose,PMB RW Program has the main target, namely social solidarity, opportunity and employment aswell as facilities, infrastructure and environmental sustainability. The method used is descriptivequalitative approach. Primary data obtained from interviews and observations, secondary dataobtained through data collection with documents. Data analysis uses data collection methods,triangulation techniques and extends field involvement. The results of the research that theeffectiveness of the implementation of PMB RW program in Senapelan sub-district PekanbaruCity is still running quite well. This is influenced by the factors of technical guidance, humanresources program implementer and the limitations of program budget.